Immunity against sexual stage Plasmodium falciparum and Plasmodium vivax parasites. Issue 1 (16th December 2019) - de Jong, Roos M.; Tebeje, Surafel K.; Meerstein‐Kessel, Lisette; Tadesse, Fitsum G.; Jore, Matthijs M.; Stone, Will; Bousema, Teun
Summary: The efficient spread of malaria from infected humans to mosquitoes is a major challenge for malaria elimination initiatives. Gametocytes are the only Plasmodium life stage infectious to mosquitoes. Here, we summarize evidence for naturally acquired anti‐gametocyte immunity and the current state of transmission blocking vaccines (TBV). Although gametocytes are intra‐erythrocytic when present in infected humans, developing Plasmodium falciparum gametocytes may express proteins on the surface of red blood cells that elicit immune responses in naturally exposed individuals. This immune response may reduce the burden of circulating gametocytes. For both P. falciparum and Plasmodium vivax, there is a solid evidence that antibodies against antigens present on the gametocyte surface, when co‐ingested with gametocytes, can influence transmission to mosquitoes. Transmission reducing immunity, reducing the burden of infection in mosquitoes, is a well‐acknowledged but poorly quantified phenomenon that forms the basis for the development of TBV. Transmission enhancing immunity, increasing the likelihood or intensity of transmission to mosquitoes, is more speculative in nature but is convincingly demonstrated for P. vivax . With the increased interest in malaria elimination, TBV and monoclonal antibodies have moved to the center stage of malaria vaccine development. Methodologies to prioritize and evaluate products are urgently needed.